Evolusi Pendidikan Klasik dan Modern Serta Kajian Terhadap Faktor-Faktor Pendidikan - Rahmadina, Sofia; Hindana, Nihna Faradila; Haq, Arinda Faradisal; Alifia, Febby Erlyta; Mahardika, I Ketut; Yusmar, Firdha; Firdausi, Soraya; Astuti, Sri Rejeki Dwi (LPPM Institut Pendidikan Nusantara Global, 2025)
The Educational theories are fundamental in developing effective teaching methods and strategies. They serve as a guide for educators to understand various aspects of the teaching-learning process, including student motivation, cognitive development, and social interactions. Key educational theories offer unique perspectives on how education should be conducted. Jean Piaget's theory of cognitive development emphasizes that children undergo four distinct stages of cognitive growth, each with unique characteristics and abilities. This theory significantly influences curriculum design and teaching methods appropriate for different cognitive levels. Albert Bandura's social learning theory highlights the importance of observation and imitation in learning. He argues that people learn many behaviors by observing others and the consequences of those behaviors, underscoring the role of social environments and peer interactions in education. Constructivism, popularized by Lev Vygotsky and Piaget, posits that learners actively construct their knowledge through interaction with their environment. This approach stresses the importance of hands-on experiences and contextual learning in developing student understanding. B.F. Skinner's behaviorism theory focuses on the role of reinforcement and punishment in shaping student behavior. According to this theory, behavior can be systematically shaped and controlled through positive and negative reinforcement. These theories, along with others such as humanism and cognitive theory, provide valuable frameworks for educators to design and implement effective teaching strategies. Understanding and applying various educational theories can create a better learning environment that supports students' holistic development.